The role of regulations on administrative and practices in improving quality of services in public organizations - Wulan I.R. Sari (Cogent Business & Management, 2017)
The purpose of the study is to explore how government regulations influence structure, process and outcome in improving quality of care. A qualitative approach and a multiple case study design are used to explore the relationship between government regulations and the quality of health care in Indonesia's public hospitals. Results show the four public hospitals are used to dealing with external regulators and regulations. These requirements from external regulators drive public hospitals to be more reactive to government regulations, rather than anticipate them and there are too many reports for external regulators. In short, government regulations influence improvements in the quality of services provided by public hospitals. However, public hospitals need to adapt those regulations to the hospital management and governance. In this sense, regulation is a breakthrough in solving the problem of public hospitals.
Keywords: 650